2014
DOI: 10.1007/s11105-014-0790-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus

Abstract: Pathogenesis-related (PR) proteins encoded by plant defense genes play key roles in plant disease-resistance responses, specialized in systemic-acquired resistance. However, their roles in the response of wheat to fungal infection are still not well known. Our earlier studies have reported that a full-length TcLr19PR1 gene (818 bp) was isolated from wheat infected by leaf rust (Puccinia triticina). Here, we showed that TcLr19PR1 was induced earlier and its expression level was higher in the incompatible intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…Therefore, MuPR1 may be regulated through different signaling pathways and regulators. In addition, it was reported that the expressions of PR genes were also induced in response to some abiotic environmental stresses, such as salt, low temperature, and certain light conditions (Edreva 2005;Gao et al 2015). Cis-acting elements involved in light, low-temperature, circadian control, and anaerobic induction responsiveness were also found in the pMuPR1 (Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, MuPR1 may be regulated through different signaling pathways and regulators. In addition, it was reported that the expressions of PR genes were also induced in response to some abiotic environmental stresses, such as salt, low temperature, and certain light conditions (Edreva 2005;Gao et al 2015). Cis-acting elements involved in light, low-temperature, circadian control, and anaerobic induction responsiveness were also found in the pMuPR1 (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed that the transcription and translation level of PR1 was significantly increased in the plants under biotic stresses (Ali et al 2018b;Shi et al 2019;Tunsagool et al 2019;Yang et al 2019). When the PR1 genes were overexpressed in different plants, the transgenic plants generally exhibit enhanced increased disease resistance toward many plant disease-causing bacteria, fungi, and even viruses, and conversely, the PR1 gene silenced plants showed more susceptibility than wild-type to pathogen infection (Cutt et al 1989;Rivière et al 2008;Kusajima et al 2010;Dolatabadi et al 2014;Gao et al 2015;Jiang et al 2015;Maschietto et al 2016;Liu et al 2019). However, up to now, there is no definite evidence that PR1 proteins directly inhibit pathogen growth (Pečenková et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The expression level of a set of genes involved in wheat defence activated either during specific resistance, after pathogen infection or resistance inducer treatment were measured by quantitative real‐time PCR (qPCR). The expression of chitinase 2‐ and glucanase‐encoding genes (GenBank accession nos , ) was induced in cultivars resistant to Z. tritici (Adhikari et al ., ; Shetty et al ., ), while the expression of pathogenesis‐related protein 1 (PR1)‐encoding gene (HQ 848391) was induced earlier and with a higher level during an incompatible interaction between wheat and Puccinia triticina than in compatible interactions (Gao et al ., ). The expression of a lipoxygenase‐encoding gene (U32428) was also studied according to the induction observed after benzothiadiazole (BTH; Görlach et al ., ) and trehalose (Tayeh et al ., ) preventive treatments, which protected wheat against Blumeria graminis f. sp .…”
Section: Introductionmentioning
confidence: 97%
“…PR1: Two genes in this gene family (PR1a and PR1b) have been cloned from both wheat and barley. PR1 showed induction by various pathogens (Görlach et al 1996;Vallélianbindschedler et al 1998;Molina et al 1999;Gao et al 2015) and was also reported as downstream of NPR1 in AR triggered by P. syringae DC3000 (Wang et al 2016). The expression level of wheat TaPR1b was much higher than that of TaPR1a in different tissues (Molina et al 1999).…”
Section: Pr and Bth-induced Genes In Wheat And Barleymentioning
confidence: 96%
“…;Molina et al (1999);Lu et al (2014);Gao et al (2015);Wang et al . (1990);Kang and Buchenauer (2002);Liu et al (2010);Wang et al .…”
mentioning
confidence: 99%